Mediastinal Follicular Dendritic Cell Sarcoma: First Case Report in Costa Rica. - Carlos Andrés Pabón-Páramo; Randall Angulo-Bolaños; Randall Rojas-Varela (Respirar, 2024)
Follicular dendritic cell sarcoma (SFCD) is a rare malignant neoplasm derived from follicular dendritic cells, which has been classified, given its immunohistochemical characteristics, as part of the group of sarcomas, where it represents less than 1%. Currently, there are less than 1000 reports in the literature worldwide, which generates a difficulty not only in diagnosis, being frequently confused with lymphoid type neoplasms; but also, as therapeutic as there is no clear consensus on its definitive management. This clinical case review describes the first reported case of SFCD in Costa Rica.